Utilization of Using Secondhands Materials as A Learning Media in Understanding Improving of Building Space Materials in Class V of Elementary School Students - Simarmata, Justin Eduardo; Hijriani, Lailin; Bantaika, Aris; Kehi, Sefrinus; Bana, Marten Luter; Sanam, Thofilus (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The aims of this community service activity is to improve students' learning ability in understanding the material of space building by utilizing secondhands materials as a learning media. Furthermore, the implementation background of this service is to improve students' reasoning power through the activity to familiarize students to solve building space problems concretely through using secondhand materials that are used as learning media. This activity consists of three steps starting with a field assessment, an implementation step and finally an evaluation step. In the field exploration step, the servant determines the activity participants, which is devoted to Fifth class of elementary school students, does administrative preparation, material questions preparation and then prepares a schedule. The second step is the implementation step in the form of a cursory exposure regarding the use of secondhand materials that can be used as a learning media for space building materials, then providing samples of space building questions for students to work on and questions discussion. The last step is the evaluation step in the form of evaluation toward activity implementation that have been compiled based on each of the tasks that have been given. Based on the activity that have been carried out, it can be concluded that this training activity increases students 'knowledge of the space building concept in a concretely and increases students' skills in working on tests related to space building. In addition, this training is to motivate students to be more active in mathematics learning.